Carbon quantum dots assisted graphene exfoliation derived activated carbon - Norshahirah Nadiah, Abd Rahman (2016)
Graphene is deemed as the strongest and toughest material since its discovery in 2004 by Andre Geim and Konstantin Novoselov as it offers exceptional potential in electronic, thermal and mechanical properties for various application in future. Graphene can be derived from any materials that have presence of carbon in its structure and can be exfoliated in various ways including wet chemicals route. However, chemical reduction of graphene from any carbon sources is highly toxic and harmful to human‟s health and environment. In this study, an environmental friendly approach to exfoliate graphene is proposed where graphene is derived from activated carbon (AC) and water as solvent through liquid phase exfoliation method. The exfoliation is assisted by sonication process where the induced microbubbles due to cavitation will collapse and release a tremendous amount of energy to exfoliate graphene from AC. Since water has high surface tension, carbon quantum dots (CQDs) is added to reduce the surface tension to the optimum range and as an exfoliation agent. The CQDs is synthesized from citric acid and urea by microwave irradiation. Dialysis process of CQDs solution is done to remove large and unreacted particles to obtained fine particle size of CQDs. The morphology of exfoliated graphene and CQDs is confirmed by FESEM analysis. The functional groups for exfoliated graphene and CQDs are determined by FT-IR (ATR) spectroscopy analysis. The concentration of exfoliated graphene obtained is calculated by linear regression equation obtained from a standard curve of graphene where 0.01177 mg/mL is produced from 24 mg of activated carbon.